PERANAN SOCIAL CAPITAL DALAM PEMBANGUNAN EKONOMI - Subejo Subejo (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2004)
In the development process worldwide, researchers and scholars these days are paying more attention to the significant role of social capital. There is a growing understanding that social capital is one of the determinant factors in the economic development. The importance of social capital as a significant factor of growth has been widely and commonly acknowledged. Social capital refers to the institutions, relationship, and norms that shape the quality and quantity of society’s social intreactions. Social capital however, is not simply the sum of the institutions, which underpain a society; it is also the glue that holds them together. It includes the shared values and rules for social cinduct expressed in personal relationship, trust, and a common sense of “civic” responsibility, that makes society more than a collection of individuals.The formal study on social capital in Indonesia is still very rare. Eventhough the terminology of social capital has not been formally used, several studies on Indonesian villagers have tried to examine types and functions of human relations and cooperation. The Indonesian peasant households still attach great importance to good relations with neighbors and relatives in their community. These relations are expressed into various types of mutual and are commonly known as gotong royong tradition.It will be much more rewarding if the further studies are able to capture and cover each element of social capital dimension in rural Indonesia. Practices of local institutions in rural Indonesia such as social service groups, labor institutions for mutual help, rotational saving groups, traditional social safety net, equalized inheritance system, share tenancy forms, and service of government affairs should be included in the more advance studies.